Characteristics of Nitric-Oxide Emissions from Traditional Flame and MILD Combustion Operating in a Laboratory-Scale Furnace - Shu, Ziyun; Wang, Feifei; Dai, Chong; Si, Jicang; Wang, Bo; Mi, Jianchun (Journal of thermal science, 2020)
This study investigated the formation and emission characteristics of nitric oxide (NO) from flameless MILD (moderate or intensive low-oxygen dilution) combustion (MILDC) versus traditional visible-flame combustion (TC) in a 30-kW furnace. Both combustion processes were experimentally operated successively in the same furnace, burning natural gas at a fixed rate of 19 kW and the equivalence ratio of 0.86. Numerical simulations of TC and MILDC were carried out to explain their distinction in the measured furnace temperature and exhaust NO emissions. Present measurements of the NO emission ( X NO ) versus a varying furnace wall temperature ( T w ) have revealed, at the first time, that the relationship of X NO ∼ T w was exponential in both TC and MILDC. By analyzing the simulated results, the average temperature over the reaction zone was identified to be the common characteristic temperature for scaling NO emissions of both cases. Moreover, relative to TC, MILDC had a fairly uniform temperature distribution and low peak temperature, thus reducing the NO emission by over 90%. The thermal-NO formation was found to contribute more than 70%–80% to the total X NO from TC while the N 2 O-intermediate route dominated the NO emission from MILDC.